1957
DOI: 10.1172/jci103538
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Insulin on Blood Levels of Infused Pentoses in Man

Abstract: In 1931 Wierzuchowski (1) showed an influence of insulin on galactose tolerance of dogs. More recently, Levine, Goldstein, Huddlestun, Klein, and Henry (2, 3) demonstrated that insulin lowers the blood levels of D-galactose, D-xylose, and L-arabinose but not of D-arabinose or D-mannose, following their infusion into the eviscerated nephrectomized dog. The volume of distribution of the responsive sugars was increased from 45 to 70 per cent of body weight as a result of insulin administration. It was suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

1957
1957
1977
1977

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…The maximum glucose values were consistently recorded 30 to 40 minutes after the end of the pentose infusions, and were followed by gradual declines of blood glucose values to or below the control concentrations. Examples of these rises of blood glucose may be seen in the companion paper by Segal, Wyngaarden, and Foley (13). Similar fusions of L-arabinose (Table I).…”
Section: Other Methodsmentioning
confidence: 80%
See 2 more Smart Citations
“…The maximum glucose values were consistently recorded 30 to 40 minutes after the end of the pentose infusions, and were followed by gradual declines of blood glucose values to or below the control concentrations. Examples of these rises of blood glucose may be seen in the companion paper by Segal, Wyngaarden, and Foley (13). Similar fusions of L-arabinose (Table I).…”
Section: Other Methodsmentioning
confidence: 80%
“…This responsiveness, interpreted by most workers as representing a facilitation of pentose transfer across cell membranes into intracellular fluid, was first thought to be restricted to those pentoses possessing a glucose-like stereochemical constitution of carbon atoms 1 to 3 (12). Recent studies have shown, however, that insulin responsiveness is not restricted to such sugars (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have described the physiological disposition of large quantities of infused pentoses (10), the effect of insulin on blood levels of infused pentoses (11) as well as studies of the metabolism of D-ribose (12). This paper reports some observations on the fate of C14 labeled D-xylOse, D-lyxose, D-arabinose and L-arabinose administered in trace quantities intravenously to normal human subjects.…”
mentioning
confidence: 97%
“…Preliminary results of these studies have been published (13), as well as a report of the hypoglycemia induced by ribose infusion (14). Previous publications (15,16) from this laboratory have described the physiologic disposition in man of the related pentoses D-Xylose, D-and L-arabinose, and D-lyxose, as well as the effects of insulin on the blood levels of these sugars.…”
mentioning
confidence: 99%